CHEESE CERTIFICATION (Western European Journal of Modern Experiments and Scientific Methods, 2025)
Protection of human life and health, as well as the environment from various harmful effects, protection of consumer interests regarding mutual exchange and compatibility of goods, elimination of barriers in international trade, and enhancement of the competitiveness of national products